Non-linear analysis of an experimental joint of column and beams of armed concrete-steel column for portics (Gaceta Técnica, 2017)
In this research, the nonlinear behavior of a real-scale experimental joint (node) is studied, consisting of three reinforced concrete elements, one column and two beams joined to a structural steel column at the upper level. In the numerical analysis the model of the union was analyzed in the inelastic range, this model was elaborated with the finite element program based on fibers, SeismoStruct to analyze as a function of time, the traction and compression efforts in the confined area and not confined area of the concrete column and in the longitudinal reinforcement steel, as well as verification of the design of the base plate that joins the two columns. The results showed that tensile stresses in the unconfined zone surpassed the concrete breaking point, with cracking occurring just below the lower edge of the beams; in the confined area the traction efforts were much lower, with cracks occurring later than in the non-confined area. The concrete column-steel column joint behaved as a rigid node, so the elastic design was consistent with the calculation methodology of base plates for steel columns.
Keywords: rigid node; inelastic study; base plate